Legality of Electronic Medical Records (RME) in Hospital Management Information System Readiness based on Minister of Health Regulation Number 24 of 2022 concerning Medical Records - Ulfa, Nadiya; Yuspin, Wardah (Soepra Jurnal Hukum Kesehatan, 2023)
Information and communication technology has developed very rapidly in various sectors including the health sector, one of which is the electronic medical record (ERME). Electronic medical records have been used in various hospitals in the world as a substitute or complement to health records in paper form. In Indonesia, improvements to rme management have begun to be implemented in several hospitals or health centers. Such is the complexity of the challenges for the implementation of the RME, it is necessary to carry out a readiness assessment prior to the implementation of the RME. Management is not always able to accept challenges and manage effectively and critically in order to make changes to information systems and new technologies. In the end, the new electronic information technology is expected to increase privacy and confidentiality. In the regulation of the Minister of Health of the Republic of Indonesia number 24 of 2022 includes: ownership and contents of electronic medical records; security and protection of electronic medical record data including the confidentiality of the contents of the electronic medical record, waiver of the rights to the contents of the electronic medical record and the storage period of the electronic medical record.